Ferraz, D., Gama, F., & Fleischer, S. (2022). 180 graus, minhas reviravoltas com o câncer de mama. (J. R. C. M. Ayres, Prefácio). (C. Siren, Ilustrações). 1. ed. Rio de Janeiro: NAU Editora.. pp. 336. - Cavalcanti, Clarissa Lemos (Campos - Revista de Antropologia, 2025)
Resenha da obra 180 graus, minhas reviravoltas com o câncer de mama.